Postcommunist Germany: Comparing Eastern Germany and Central and Eastern Europe's Political Development. - Aron, Hadas (German Politics & Society)
This article situates Germany within postcommunist Central and Eastern Europe (CEE) to explain current political outcomes, particularly, the disproportionate success of the AfD in eastern Germany. Similar to CEE, politics in eastern Germany is fragmented and volatile compared to western Germany; the political system in the east reflects conservative social values; and east German patterns of discontent are similar to CEE. However, in CEE, party systems were new and thus volatile and susceptible to populist mobilization from both mainstream and radical parties. Conversely, East Germany integrated into the developed West German party system and adopted its traditional parties, lowering the east's potential for volatility and polarization. Moreover, since the east is a minority within Germany, its relative volatility has limited impact on the German system.